A randomised scheme for secured modular exponentiation against power analysis attacks. Issue 4 (2nd October 2019) - Barman, Moushumi; Mahanta, Hridoy Jyoti
ABSTRACT: This paper presents an approach to compute secured modular exponentiation to mitigate power analysis attacks. Two processes have been designed based on 'multiply-always' binary method, which injects dummy multiplications so that the original multiplications can remain intact. The two processes are being invoked based on a random variable, which generated either 0 or 1. With these randomised modular exponentiation, the proposed approach can resist simple and differential power analysis attacks to a large extent. The proposed approach has been implemented using conventional 'squaring-multiplication' and 'Montgomery-Ladder' methods. Further, the work has also been extended to CRT-RSA, which is widely used for fast computation. The proposed method has been implemented for different key sizes of 1024-bit, 1536-bit and 2048-bit RSA & CRT-RSA. The analysis and results show that with a complexity of O ( n ), the proposed approach can resist some of the standard DPA attacks on modular exponentiation.